John Rawls on redistribution and recognition - Aguayo, Pablo (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2020)
In this paper, I argue that in the context of the redistribution-recognition debate, Rawls developed a theory of justice that exceeds the margins of allocative justice and has good arguments to deal with demands of social change and recognition. I propose that some criticism of the Rawlsian conception of social justice confuses allocative justice with distributive justice. In doing this, they not only understand Rawls’s conception of primary goods as measuring staff, but they also reject their moral dimension. Finally, I examine the concepts of reciprocal recognition and self-respect to improve and expand the discussion about Rawlsian distributive justice.